Surviving Vulnerabilities of Isolation among Widowed Empty Nesters - Ablanque, Argonne Robert A.; Singson, Deborah Natalia E. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
A sufficient number of empty nesters living in isolation had been increasing in population, thus it is encouraged to provide a plethora of research data and studies on gerontology and isolation that could contribute to their wellbeing. This study utilized the descriptive phenomenological analysis and purposive sampling method to determine the five participants. Inclusion criteria were established to narrow down participants with common conditions. Data were gathered through online interviews and analyzed using Lichtman’s 3 C’s comprised of codes, categories, and concepts. The following themes emerged: economic vulnerability, physical vulnerability, social vulnerability, emotional vulnerability, coping with isolation vulnerabilities, and hopeful aspirations. In conclusion, empty nesters may experience multiple challenges that made them vulnerable in many aspects, but they were also able to develop coping strategies to manage these vulnerabilities. The limitations encountered in this study may be improved by exploring the experiences of empty nesters from other socio-economic categories and conducting a mixed-method study that would generate a broad range of data. The result of the study exposes various vulnerabilities that contribute to challenges encountered by empty nesters. Since the results are limited from generalizing the entire senior citizen population, it could be noted that the resiliency to survive challenging situations promote a holistic approach for aging and positive psychology as results provided varied sources for coping which ranges from both the internal and external sources. Survival elements of connectedness and transcending difficult situations affirm the practicality of promoting life meaning especially during difficult situations.